2012
DOI: 10.1002/ange.201107398
|View full text |Cite
|
Sign up to set email alerts
|

Die 1,1‐Carboborierung von Bis(alkinyl)phosphanen als Zugang zum Phospholgerüst

Abstract: Wir danken der Deutschen Forschungsgemeinschaft für die Fçrderung unserer Arbeit. J.M. dankt der NRW Research School (Universität Münster) für ein Stipendium. K.U. dankt JSPS und der International Research Training Group Münster/Nagoya für ein Stipendium und Unterstützung. Hintergrundinformationen zu diesem Beitrag sind im WWW unter http://dx.doi.org/10.1002/ange.201107398 zu finden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…We and others had previously shown that siloles [2,8] or phospholes [9] can readily be obtained by a series of consecu- In any case, hydride transfer from the diisopropylamino substituent to the distal carbon atom of the second [B]-acetylene substituent represents the favored pathway to give the products 10. These show a framework similar to that of the compound type B mentioned in the introduction (see Scheme 1), but it is has been formed in quite a different reaction sequence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We and others had previously shown that siloles [2,8] or phospholes [9] can readily be obtained by a series of consecu- In any case, hydride transfer from the diisopropylamino substituent to the distal carbon atom of the second [B]-acetylene substituent represents the favored pathway to give the products 10. These show a framework similar to that of the compound type B mentioned in the introduction (see Scheme 1), but it is has been formed in quite a different reaction sequence.…”
Section: Discussionmentioning
confidence: 99%
“…We and others had previously shown that siloles2, 8 or phospholes9 can readily be obtained by a series of consecutive 1,1‐carboboration reactions starting from the respective bis(alkynyl)silanes or ‐phosphanes. The bis(alkynyl)aminoborane 7 /B(C 6 F 5 ) 3 systems investigated in this study could have offered a similar pathway to borole systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations